2012
DOI: 10.1186/1749-8104-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Neurog1 and Neurog2 coordinately regulate development of the olfactory system

Abstract: BackgroundProneural genes encode basic helix–loop–helix transcription factors that specify distinct neuronal identities in different regions of the nervous system. In the embryonic telencephalon, the proneural genes Neurog1 and Neurog2 specify a dorsal regional identity and glutamatergic projection neuron phenotype in the presumptive neocortex, but their roles in cell fate specification in the olfactory bulb, which is also partly derived from dorsal telencephalic progenitors, have yet to be assessed. Given tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 91 publications
0
29
1
1
Order By: Relevance
“…2). Because the half-life of GFP is relatively longer than the transcription factors 30 , we can label cells derived from Olig2 + and Gsx1 + cells using GFP expressed under the control of endogenous Olig2 and Gsx1 promoters, respectively. In the E12.5 cerebella of Olig2 GFP/ + embryos, GFP-labelled cells derived from the Olig2 + cells expressed Corl2 but not Pax2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). Because the half-life of GFP is relatively longer than the transcription factors 30 , we can label cells derived from Olig2 + and Gsx1 + cells using GFP expressed under the control of endogenous Olig2 and Gsx1 promoters, respectively. In the E12.5 cerebella of Olig2 GFP/ + embryos, GFP-labelled cells derived from the Olig2 + cells expressed Corl2 but not Pax2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Neurog2 specifies a dorsal regional identity and glutamatergic neurotransmitter phenotype in the neocortex [35,36]. It has been reported that Neurog2 regulates the development of the olfactory system [37] and the dentate gyrus [38]. It is well known that the dentate gyrus is a major component of the hippocampal formation and is essential for normal hippocampal function.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these factors, starting with Ascl1, followed by Neurog1 and NeuroD1, have been shown to indicate neuronal specification in the epithelium, as in the central nervous system (CNS) (Chen et al, 2014; Goldstein et al, 2015; Huard et al, 1998; Jang et al, 2003; Joiner et al, 2015; Krolewski et al, 2012; Leung et al, 2007; Manglapus et al, 2004; Packard et al, 2011a, 2016; Shaker et al, 2012; Xie et al, 2016). These neurogenic factors act in opposition to drivers of non-neuronal cell differentiation such as Hes1, which directs the formation of Sus cells(Cau et al, 1997; Guillemot and Joyner, 1993; Krolewski et al, 2012; Packard et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%